2020
DOI: 10.1002/ange.201913712
|View full text |Cite
|
Sign up to set email alerts
|

Image‐Based Morphological Profiling Identifies a Lysosomotropic, Iron‐Sequestering Autophagy Inhibitor

Abstract: Chemical proteomics is widely applied in small‐molecule target identification. However, in general it does not identify non‐protein small‐molecule targets, and thus, alternative methods for target identification are in high demand. We report the discovery of the autophagy inhibitor autoquin and the identification of its molecular mode of action using image‐based morphological profiling in the cell painting assay. A compound‐induced fingerprint representing changes in 579 cellular parameters revealed that autoq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…It selectively kills CSC by sequestering lysosomal iron, leading to the production of reactive oxygen species (ROS) via Fenton chemistry, lysosomal membrane permeabilization and subsequent cell death reminiscent of ferroptosis . Thus, strategies to retain iron in lysosomes represent an attractive therapeutic modalities to target and eradicate CSC. A key protein in the regulation of iron homeostasis is the divalent metal transporter 1 (DMT1) located within the plasma membrane and membranes of late endosomes and lysosomes, which enables the translocation of ferrous iron (Fe 2+ ) to the cytosol following iron endocytosis .…”
Section: Methodsmentioning
confidence: 99%
“…It selectively kills CSC by sequestering lysosomal iron, leading to the production of reactive oxygen species (ROS) via Fenton chemistry, lysosomal membrane permeabilization and subsequent cell death reminiscent of ferroptosis . Thus, strategies to retain iron in lysosomes represent an attractive therapeutic modalities to target and eradicate CSC. A key protein in the regulation of iron homeostasis is the divalent metal transporter 1 (DMT1) located within the plasma membrane and membranes of late endosomes and lysosomes, which enables the translocation of ferrous iron (Fe 2+ ) to the cytosol following iron endocytosis .…”
Section: Methodsmentioning
confidence: 99%
“…Seventeen out of twenty nine (59 %) compounds had an induction value of >5 % at either 10 or 30 μM, confirming the library had a high degree of bioactivity overall (Table 1). [23] It has previously been shown that the cell painting assay can predict certain modes‐of‐action with high confidence, including lysosomotropism, [10,11] mitochondrial respiratory activity, [16,24] and modulation of tubulin polymerization [25] . This is due to the availability of reference compounds that closely cluster in relation to their biological fingerprint in the CPA [26] .…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, image‐based morphological profiling strategies such as the cell painting assay (CPA) have been developed to identify biological activity in a more general sense [7–9] . By comparing changes in cellular and organellar morphology upon compound treatment, one can not only determine whether a compound is bioactive, but also whether it is similar to known sets of reference compounds, facilitating mode‐of‐action and target identification [10,11] …”
Section: Introductionmentioning
confidence: 99%
“…25 It monitors bioactivity in a very broad sense and, has been proven to be a highly valuable method for comparison of bioactivity for PNPs with different fragment combinations, connectivities and stereoisomeric relationships. [26][27][28][29][30] Briefly, treated and untreated U2OS cells are stained with 6 different stains that are specific for different compartments of the cell, and imaged in 5 different channels by microscope. The images are then processed with CellProfiler 31 and further analyzed using in-house written scripts during which the single-cell data is aggregated to compound level.…”
Section: Enamine-pnp Cpamentioning
confidence: 99%